2017
DOI: 10.1016/j.celrep.2017.09.035
|View full text |Cite
|
Sign up to set email alerts
|

DMS-Seq for In Vivo Genome-wide Mapping of Protein-DNA Interactions and Nucleosome Centers

Abstract: Protein-DNA interactions provide the basis for chromatin structure and gene regulation. Comprehensive identification of protein-occupied sites is thus vital to an in-depth understanding of genome function. Dimethyl sulfate (DMS) is a chemical probe that has long been used to detect footprints of DNA-bound proteins in vitro and in vivo. Here, we describe a genomic footprinting method, dimethyl sulfate sequencing (DMS-seq), which exploits the cell-permeable nature of DMS to obviate the need for nuclear isolation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Figure 2 shows this chemistry and also denotes whether the reactions directly result in a stop during reverse transcription or whether additional reactions are needed to read out the base-pairing status of the nucleotide. Probes have been identified that react with the Watson-Crick, Hoogsteen, and sugar faces of the base, the ribose sugar, and the phosphate, as reviewed in Ehresmann et al (1987) with recent advances presented in , Spitale et al (2013), Umeyama and Ito (2017), Feng et al (2018), and Mitchell et al (2018). Dimethyl sulfate (DMS) reacts with A(N1) and C(N3) on the Watson-Crick face, as well as G(N7) and A(N3) in the major and minor grooves, respectively, where it has also been used to probe dsDNA (Lawley and Brookes 1963;Umeyama and Ito 2017).…”
Section: Technique: the Chemistry Of Probing Rna Structurementioning
confidence: 99%
See 2 more Smart Citations
“…Figure 2 shows this chemistry and also denotes whether the reactions directly result in a stop during reverse transcription or whether additional reactions are needed to read out the base-pairing status of the nucleotide. Probes have been identified that react with the Watson-Crick, Hoogsteen, and sugar faces of the base, the ribose sugar, and the phosphate, as reviewed in Ehresmann et al (1987) with recent advances presented in , Spitale et al (2013), Umeyama and Ito (2017), Feng et al (2018), and Mitchell et al (2018). Dimethyl sulfate (DMS) reacts with A(N1) and C(N3) on the Watson-Crick face, as well as G(N7) and A(N3) in the major and minor grooves, respectively, where it has also been used to probe dsDNA (Lawley and Brookes 1963;Umeyama and Ito 2017).…”
Section: Technique: the Chemistry Of Probing Rna Structurementioning
confidence: 99%
“…Probes have been identified that react with the Watson-Crick, Hoogsteen, and sugar faces of the base, the ribose sugar, and the phosphate, as reviewed in Ehresmann et al (1987) with recent advances presented in , Spitale et al (2013), Umeyama and Ito (2017), Feng et al (2018), and Mitchell et al (2018). Dimethyl sulfate (DMS) reacts with A(N1) and C(N3) on the Watson-Crick face, as well as G(N7) and A(N3) in the major and minor grooves, respectively, where it has also been used to probe dsDNA (Lawley and Brookes 1963;Umeyama and Ito 2017). Kethoxal is used to probe the Watson-Crick face of G, whereas selective 2 ′ -hydroxyl (2 ′ -OH) acylation analyzed by primer extension (SHAPE) reacts with the 2 ′ -OH ) and light-activated structural examination of RNA (LASER) modifies the C8 position of purines (G>A) (Feng et al 2018).…”
Section: Technique: the Chemistry Of Probing Rna Structurementioning
confidence: 99%
See 1 more Smart Citation
“…This simple consideration led us to develop DMS-seq. DMSseq can detect in vivo binding sites for various trans-acting factors, notably without isolating nuclei (Umeyama & Ito, 2017).…”
Section: Background Informationmentioning
confidence: 99%
“…Then, using omics technologies, we can obtain genome-wide information about the adaptive phenotypic and genotypic changes resulting from the selective pressure. Advances in omics technologies (Bentley et al 2008;Nagalakshmi et al 2008;Bennett et al 2009;Bamba et al 2012;Matsumoto et al 2017;Umeyama and Ito 2017;Miura et al 2019) have made ALE a powerful approach for analyzing evolutionary biology as well as for breeding useful microorganisms (Conrad et al 2011;Jiang et al 2012;Tokuyama et al 2018), and understanding stress-tolerant mechanisms (Dragosits and Mattanovich 2013;Winkler and Kao 2014;Horinouchi et al 2017a), or analyzing antibiotic-resistant evolution (Lenski 1998;Lazar et al 2014;Gillings et al 2017;Levin-Reisman et al 2017;Zampieri et al 2017;Furusawa et al 2018). For example, ALE of microorganisms for higher temperature (Bennett et al 1990;Leroi et al 1994;Bennett and Lenski 2007;Kishimoto et al 2010;Ying et al 2015), various stressors (Atsumi et al 2010;Reyes et al 2013;Harden et al 2015;Matsusako et al 2017), and alternativesubstrates (Lee and Palsson 2010) was performed previously.…”
Section: Introductionmentioning
confidence: 99%